Ideology and Communication Strategy of Indonesia’s 2024 Presidential Candidates: A Transitivity Analysis - Supatmiwati, Diah; Hastuti, Hilda; Indra, Indra; Fissilmi, Annisa; Zuhroni, Zuhroni; Putri, Tiara Resta (LPPM Universitas Bumigora Mataram, 2025)
The purpose of this study is to investigate presidential candidates’ ideologies and strategies of communication though the type of transitivity processes in their speech on the last presidential debate. The final debate of presidential candidates in 2024, all Candidates used languages to shape public opinion and persuade the audience. Critical discourse analysis (CDA) reveals hidden meanings or agenda of the candidates in debate. It examines how language supports power dynamics, social hierarchies, and ideologies. Those are expressed through text and speech in social and political contexts. The method used in this research is descriptive qualitative. The research began with the observation of the speeches of the candidates on an official video. Secondly, the data was subjected to a critical discourse analysis. This analysis was used to determine how the candidates presented themselves in terms of their different and common ideologies. The research findings revealed that six types of transitivity processes were found in the candidates’ speeches, with material processes dominating and then there was also a structural analysis that revealed that all candidates used different types of processes to display their respective leadership styles. Each Candidate’s reveals different ideologies, language patterns and political communication strategies that boosts persuasive and reveals the link between language, power, and ideology. It shows how all candidates create messages that resonate with voters, influencing public opinion and prompting action. Furthermore, the result of this research is to provide insight into the linguistic construction of political ideology and power in Indonesian politicaldiscourse.